Interactive Effects of Ocean Acidification and Warming on Growth, Fitness and Survival of the Cold-Water Coral Lophelia pertusa under Different Food Availabilities - Büscher, Janina V.; Form, Armin U.; Riebesell, Ulf (Frontiers in Marine Science, 2017)
Cold-water corals are important bioengineers that provide structural habitat for a diverse species community. About 70 % of the presently known scleractinian cold-water corals are expected to be exposed to corrosive waters by the end of this century due to ocean acidification. At the same time, the corals will experience a steady warming of their environment. Studies on the sensitivity of cold-water corals to climate change mainly concentrated on single stressors in short-term incubation approaches, thus not accounting for possible long-term acclimatisation and the interactive effects of multiple stressors. Besides, preceding studies did not test for possible compensatory effects of a change in food availability. In this study a multifactorial long-term experiment (6 months) was conducted with end-of-the-century scenarios of elevated pCO2 and temperature levels in order to examine the acclimatisation potential of the cosmopolitan cold-water coral Lophelia pertusa to future climate change related threats. For the first time multiple ocean change impacts including the role of the nutritional status were tested on L. pertusa with regard to growth, ‘fitness’, and survival. Our results show that while L. pertusa is capable of calcifying under elevated CO2 and temperature, its condition (fitness) is more strongly influenced by food availability rather than changes in seawater chemistry. Whereas growth rates increased at elevated temperature (+ 4°C), they decreased under elevated CO2 concentrations (~ 800 µatm). No difference in net growth was detected when corals were exposed to the combination of increased CO2 and temperature compared to ambient conditions. A 10-fold higher food supply stimulated growth under elevated temperature, which was not observed in the combined treatment. This indicates that increased food supply does not compensate for adverse effects of ocean acidification and underlines the importance of considering the nutritional status in studies investigating organism responses under environmental changes.